Positive psychotherapy for distressed cancer survivors: Posttraumatic growth facilitation reduces posttraumatic stress - Ochoa, Cristian (Int J Clin Health Psychol, 2017)
There is increasing evidence that positive life changes, such as posttraumatic growth (PTG), can result from the experience of coping with cancer. However, no interventions have been specifically designed to facilitate the development of PTG in cancer. In this article, we describe and assess the results of Positive Psychotherapy for Cancer (PPC) survivors. It aims to facilitate PTG as a way of achieving significant reductions in the symptoms of emotional distress and posttraumatic stress. In addition, the corroboration of this PTG facilitation is assessed using interpersonal indicators. Method: We allocated 126 consecutive survivors of cancer with high levels of emotional distress and who were seeking psychological support to either an experimental group (PPC) or a waiting list group. Results: The PPC group obtained significantly better results after treatment than the control group, showing reduced distress, decreased posttraumatic symptoms, and increased PTG. The benefits were maintained at 3 and 12 months’ follow-up. Participants’ PTG was correlated to the PTG that their significant others attributed to them, corroborating PTG facilitation. Conclusions: PPC appears to promote significant long-term PTG and can reduce emotional distress and posttraumatic stress in cancer survivors. In addition, PTG facilitation induced by PPC is corroborated by significant others.